DOSE DELIVERY EQUIVALENCE - Benazzouz, Karim; Fzger, Czline; Regolini, Paulina; Dominicy-Lenoble, Eric; Laurent, Philippe E; Berube, Julie (Pharma, 2008)
A glass prefilled syringe is both a drug container and a drug delivery system. Consistency and accuracy of delivered fluid volume in a subject's body are key characteristics of the injection system performance. Taking the syringe's critical drug containment fuction into account, the need to include healthcare worker safety protection features is also important and has been addressed by the medical technology industry.